Controlling i zarządzanie projektami w przedsiębiorstwach budowlanych - Sieradzka-Widz, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The building enterprises base their activity on building contracts (building projects). This article presents Project Management and controlling as modern instruments, thanks which building enterprises can construct competitive superiority on market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 375-379